Establishing Geographies of Children and Young People - Skelton, Tracey; Aitken, Stuart C. (Geographies of Children and Young People, 2019)
Children's and young people's geographies is one of the most recent sub-disciplines within human geography. It has rapidly developed to a level of critical mass which includes established academic work, key names within academia, growing numbers of graduate students, expanding numbers of university level taught courses, as well as national and international training programmes focusing on younger people. In addition to the journal Children's Geographies, all the major academic presses have published monographs, textbooks and edited collections focusing on children and young people. However, the largest international collection of scholarly work on geographies of children and young people is now available through the Springer Major Reference Work, Geographies of Children and Young People. This edited collection comprises twelve volumes containing almost 300 chapters. The volumes and sections are structured by themes, which reflect the broader geographical debates, geographical diversity, and scholarly expertise of 24 editors and chapter contributors.